2001
DOI: 10.1046/j.1365-2265.2001.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility leucocyte antigens and closely linked immunomodulatory genes in autoimmune thyroid disease

Abstract: These results show that, of the polymorphisms tested within the MHC, GD is most strongly associated with DRB1*03, and associations with other immunoregulatory genes previously described in Caucasian subjects most likely reflect linkage disequilibrium. AIH differs from GD, being less influenced by the MHC region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 55 publications
5
56
2
2
Order By: Relevance
“…Our results also revealed no relation between HT and DQB1*303 or DQB1*0201 (Table 1 in the "Appendix"). These findings are almost similar to the study done by Hunt et al (2001) on 77 UK patients that showed only a weak relation between HT and DQB1*303. Data on HLA haplotypes and their association with HT have been less definitive than those on GD (Vaidya et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Our results also revealed no relation between HT and DQB1*303 or DQB1*0201 (Table 1 in the "Appendix"). These findings are almost similar to the study done by Hunt et al (2001) on 77 UK patients that showed only a weak relation between HT and DQB1*303. Data on HLA haplotypes and their association with HT have been less definitive than those on GD (Vaidya et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…For example, the development of GD could be due to the genetic effects of MHC such as DRB1*03 with OR values 2.3-3.4 (44). The genotype A5.1/A5.1 in MICA gene occurred more frequently in patients with GD than in the controls (OR 2.0) (45).…”
Section: Graves' N (%)mentioning
confidence: 99%
“…For example, studies with a small number of patients may generate high ORs. The OR of the development of GD with MHC gene is 2.3-3.4 in 135 GD patients (44), while that with MICA gene is 2.0 in 129 GD patients (45), that with CD40 gene is 1.9 in 301 GD patients (47), that with TG gene is 2.44-2.58 in 186 GD patients (30), and that with TNF-a gene is 2.94 in 173 GD patients (34). On the other hand, the OR of the development of GD with CTLA-4 gene is 1.49 PD-L1, programmed cell death-ligand 1; SNP, single nucleotide polymorphism; ATD, antithyroid drugs.…”
Section: Graves' N (%)mentioning
confidence: 99%
“…Both genetic and environmental factors may affect the development of Graves' disease. Such an autoimmune mechanism could be associated with HLA on chromosome 6p [5][6][7][8][9][10][11][12][13][24][25][26][27][28][29][30][31][32][33] and CTLA-4 on chromosome 2q33 [14][15][16][17][18]. There are several different results regarding HLA haplotypes associated with Graves' disease in Japan [13,28,29,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature HLA typing has a strong association with the development of Graves' disease with childhood onset, but CTLA-4 polymorphism does not [13]. In addition, HLA polymorphism associated with Graves' disease is different between childhood and adult onset [5][6][7][8][9][10][11][12][13][24][25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%